THE INFLUENCE OF CONVENIENCE AND PRICE ON REPURCHASE INTEREST AT RAMAYANA TEBING TINGGI SUPERMARKET - Alif Tromi Gulo; Angga Fitra Hadi; Markahasa Timbul; Imelda Mardayanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine the Effect of Convenience and Price on Repurchase Interest at the Ramayana Tebing Tinggi Supermarket. The analysis method used in this study is to use an instrument test, namely validity and reliability tests. Classic assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, determination coefficient analysis (R2), hypothesis tests, namely the T test and F test. The results of the study indicate that Convenience Affects Repurchase Interest at the Ramayana Tebing Tinggi Supermarket, Price Does Not Affect Repurchase Interest at the Ramayana Tebing Tinggi Supermarket, Convenience and Price Influence Simultaneously on Repurchase Interest at the Ramayana Tebing Tinggi Supermarket.